Growing up in the world next door - Springbett, David; MacAndrew, Heather; Asterisk Productions (Oley, PA : Bullfrog Films, 1988)
Find out what it means to come of age in the Third World today. This program explores the lives of three teenagers, one from Nepal, one from Kenya and one from St. Vincent
Copy in DVD Format
Editor, David Leach
Narrator: Murray Cruchley
VHS Format
Keywords: Teenagers -- Developing countries; Teenagers -- Nepal; Teenagers -- Kenya; Teenagers -- Saint Vincent